Generalisation of close-to-convex of complex order - Khalida Inayat Noor,; Saqib Hussain, (Penerbit ukm, 2010)
Using the concept of operator I µ(> - 1,µ>0 ), we study some new classes of analytic functions. Some inclusion relationships are investigated. We also show that these classes are closed under convolution with a convex function. An application of the results is also discussed